2019
DOI: 10.1002/jcp.28573
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic effects of exosomes in γ‐herpesvirus‐associated neoplasms

Abstract: Kaposi's sarcoma-associated herpesvirus (KSHV) and Epstein-Barr virus (EBV) are herpesviruses associated with human malignancies. As exosomes can shuttle many herpesvirus-associated biomolecules from host cells to recipient cells, the exosomal pathway is utilized by herpesviruses to achieve extensive infections and even oncogenesis. In this review, we discuss the oncogenic biomolecules present in exosomes derived from KSHV-and EBV-infected cells. Moreover, oncogenesis via exosomal biomolecules mainly occurs th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 104 publications
1
11
0
Order By: Relevance
“…Indeed, EVs display a multifaceted role in viral infections, contributing in first place to viral replication, dissemination, and immune evasion modulating the host immune system activation. Furthermore, EVs may block (Ipinmoroti and Matthews, 2020) or otherwise trigger the antiviral response, exacerbating the damage and causing several detrimental effects, such as oncogenesis (Zheng et al, 2019), inflammation (Sadri Nahand et al, 2020) or autoimmune responses (Gunasekaran et al, 2020). Several viruses exploit intracellular membrane rearrangements, creating peculiar double-membrane structures known as "replicative organelles", to complete their replication facilitating new virions formation and budding from the host cell (Wolff et al, 2020).…”
Section: Evs and Viral Infections: A Multifaceted Interplaymentioning
confidence: 99%
“…Indeed, EVs display a multifaceted role in viral infections, contributing in first place to viral replication, dissemination, and immune evasion modulating the host immune system activation. Furthermore, EVs may block (Ipinmoroti and Matthews, 2020) or otherwise trigger the antiviral response, exacerbating the damage and causing several detrimental effects, such as oncogenesis (Zheng et al, 2019), inflammation (Sadri Nahand et al, 2020) or autoimmune responses (Gunasekaran et al, 2020). Several viruses exploit intracellular membrane rearrangements, creating peculiar double-membrane structures known as "replicative organelles", to complete their replication facilitating new virions formation and budding from the host cell (Wolff et al, 2020).…”
Section: Evs and Viral Infections: A Multifaceted Interplaymentioning
confidence: 99%
“…In this regard, exosomes are one of the favorite tools of gamma herpes viruses. Using them can manipulate the tumor microenvironment through three processes: regulation of downstream signaling pathways, lack of recognition by the immune system, and transformation of cells [ 158 ]. Some studies have reported that these viruses have significant impacts on the content of exosomes and their cargo and that these alterations have the potential to spread viral infection, metabolism, translation, migration, and chromatin modeling and enhance tumorigenesis [ 159 ].…”
Section: The Role Of Exosomes In Human Oncogenic Viruses-associated C...mentioning
confidence: 99%
“…Oncogenig effect gamma-herpes virus (Zheng et al, 2019), human papillomavirus (Honegger et al, 2015;Ambrosio et al, 2019;Chiantore et al, 2020), HIV (Sharma, 2019), MVP (Teng et al, 2017) Accumulation of beta amyloid plaques HIV (Fulop et al, 2019). Trigger inflammation human papillomavirus (Sadri Nahand et al, 2019) Contribute to tissue fybrosis HCV (Kim et al, 2019).…”
Section: Mechanism Virusmentioning
confidence: 99%
“…EVs secreted during the course of a viral infection can have effects in many parts of the body, triggering secondary diseases (Table 1). For example, gamma-herpes virus can induce an oncogenic effect (Zheng et al, 2019), among several others. There is also evidence that EVs contribute to the beta-amyloid plaque accumulation that occurs in the brain of HIV patients, probably contributing to cognitive decline (Fulop et al, 2019).…”
Section: Evs Secreted During Viral Infections Can Cause Secondary Dismentioning
confidence: 99%